2009
DOI: 10.3390/m622
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavonoid Glycoside from Salix denticulata Aerial Parts

Abstract: A new flavonoid glycoside (1) has been isolated from the aerial parts of Salix denticulata (Salicaceae) together with five known compounds, β-sitosterol, 2,6-dihydroxy- 4-methoxy acetophenone, eugenol-1-O-β-D-glucopyranoside, 1-O-β-D-(3’-benzoyl) salicyl alcohol and luteolin-7-O-β-D-glucopyranosyl-(1-6)-glucopyranoside. The structure of 1 was elucidated as 2’,5-dihydroxy-3’-methoxyflavone-7-O-β-D-glucopyranoside by means of chemical and spectral data including 2D NMR studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…leaves (Tawfeek et al, 2019), respectively. Compounds (12, 14) were reported in S. denticulate leaves (Rawat et al, 2009;Semwal et al, 2011). S. gilgiana Seemen.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…leaves (Tawfeek et al, 2019), respectively. Compounds (12, 14) were reported in S. denticulate leaves (Rawat et al, 2009;Semwal et al, 2011). S. gilgiana Seemen.…”
Section: Flavonoidsmentioning
confidence: 99%
“…bark, leaves and flowers (El-Shazly et al, 2012;Sobeh et al, 2019), S. subserrata Willd. leaves (Balbaa et al, 1979), S. denticulate erial parts (Rawat et al, 2009), S. babylonica L. roots (Singh et al, 2017), S. subserrata Willd. bark and leaves (Hussain et al, 2011).…”
Section: Sterols and Terpenesmentioning
confidence: 99%
“…The plants from Salix genus are known also contain flavonoids, such as 2',5-dihydroxy-4'methoxyflavone-7-O-β-D-glucopyranoside that has been isolated from Salix denticulate [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the good biological activities of Salix tetrasperma Roxb such as antibacterial, anti-fungal [8], antidiabetic, antinociceptive, antipyretic [9], antiinflammatory [10], hypoglycaemic [11], [12], insecticidal, in vivo cytotoxicity [12], laxative, diuretic [13], analgesic, and antischistosomal [14]. These biological activities were influenced by the secondary metabolites such as flavonoid [7] and phenolic compounds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the correlation spectroscopy (COSY and HMBC) placed the two OCH 3 groups at C-3c and C-4c of the B ring in compound 1 [8]. Based on the foregoing analyses and comparison of the spectral data with those of compound 2 isolated from Salix denticulate [9], the structure of compound 1 was established as 5,2c-dihydroxy-3c,4c-dimethoxyflavone-7-O-E-D-glucopyranoside. The small variation between the NMR data of 1 and 2 (Table 1) was possibly due to different substitution patterns in the B ring and the solvent effect.…”
mentioning
confidence: 99%